2018
DOI: 10.1016/j.matlet.2018.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silver catalyst concentration in metal assisted chemical etching of silicon

Abstract: A systematic investigation is performed to determine the effects of the concentration of silver on metal assisted chemical etching (MaCE) on nanostructure formation mechanisms on silicon as well as their resultant optical properties. Silver nitrate concentrations of 0.008M, 0.004M, 0.003M and 0.002M with hydrogen fluoride were used for the preparation of p-type silicon nanostructures. Experimentally it is observed that when the catalysis molarity concentration is decreased in the etching processes, it resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…Graded mesoporous Si nanostructures have previously been observed to exhibit reduced recombination losses compared to Si nanowires (SiNWs) [12]. Optimized silver loading conditions were utilized to obtain mesoporous Si, more detail on the effect of silver loading on the nanostructure morphology can be found elsewhere [25]. Figure 1(a) shows the morphology and surface coverage of Ag nanoparticles (AgNPs) on CP5 polished-reference sample.…”
Section: Structural Properties Of Ag Nanoparticles (Agnps)mentioning
confidence: 99%
“…Graded mesoporous Si nanostructures have previously been observed to exhibit reduced recombination losses compared to Si nanowires (SiNWs) [12]. Optimized silver loading conditions were utilized to obtain mesoporous Si, more detail on the effect of silver loading on the nanostructure morphology can be found elsewhere [25]. Figure 1(a) shows the morphology and surface coverage of Ag nanoparticles (AgNPs) on CP5 polished-reference sample.…”
Section: Structural Properties Of Ag Nanoparticles (Agnps)mentioning
confidence: 99%
“…Furthermore, b-Si allows the adoption of the diamond wire sawing technology for mc-Si block wafering [25], which is broadly used for Cz-Si ingot wafering since it reduces the kerf-losses compared to the slurry-based wafering. Note that other b-Si etching technologies currently employed in the PV industry require additional steps for the b-Si etching process, i.e., metal-assisted chemical etching (MACE) [32,41,42] or atmospheric dry etching (ADE) [43]. Furthermore, it has been shown that black mc-Si etched by DRIE can be directly effectively passivated via double-side atomic layer deposition (ALD) [44,45], which further contributes to reducing the number of processing steps necessary for mc-Si PERC cells.…”
Section: Perc Production Processmentioning
confidence: 99%
“…Black-Si was commonly accepted as the nano-and micro-structured silicon surfaces that effectively suppress reflection, while simultaneously enhancing the scattering and absorption of light and a black look instead of a silver-gray look of pure silver wafer [3]. Until now, diverse methods have been proposed for the formation of black-Si including reactive ion etching (RIE) [4], metal-assisted etching with gold [5] or silver [6] nanoparticles, electrochemical etching, etc. The black-Si formation using one- [7] or two- [8] step nickel nanoparticlesassisted etching was also demonstrated.…”
Section: Introductionmentioning
confidence: 99%